Penyebaran Islam Di Nusantara Antara Kultur Dan Struktur - taufik nugroho; Cipto Sembodo; Ibroheem Ha; Muhammaridwan Lehnuh; Usman Madami (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2021)
In the course of its history, Islam in Nusantara has struggled with sosial realities for approximately 8 centuries. Islam in Nusantara has participated in coloring the sosial life of the Nusantaran people. The development of Islam in Nusantara is so fast and peaceful. This is something unique in history. a number of orientalist experts say that the main and first motive for the spread of Islam is wealth and power. However, archaeological data informs that Islam in Nusantara states otherwise. Even though Islam in Nusantara does not hold the reins of power, it continues to develop well in society. The da'i when spreading Islam, without adequate financial rewards, they often have to sacrifice material for the smooth running of da'wah. They also adapt to local socio-cultural conditions. Due to a natural process, archaeological facts inform that Islam in Nusantara often holds the reins of power, although this is not the main goal.